2015
DOI: 10.5539/ibr.v8n12p96
|View full text |Cite
|
Sign up to set email alerts
|

Is a MBA Degree Necessary to Be a CEO of Large Corporation: The Case of Fortune Magazine Global Top 100 Corporations?

Abstract: <p>The purpose of this paper is to examine if Chief Executive Officer (CEO) educational level particularly MBA has an impact on the performance of organizations or not. Top hundred companies around the world, who are leading and generating revenue in billion dollars per annum, either their CEO’s are MBA holders to make enough strong strategies for growth. The analysis is based upon the data collected form top 100 companies. The data consist of size of company, no of employees, industry, sector, CEO’s gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…There are no rulebooks demanding that CEOs should have a degree of post-graduation or that they must have joined college. Nonetheless, not many individuals these days make it to the peak of the business ladder in the absenteeism of formal education (Zandi et al , 2015) (Table III).…”
Section: Related Literaturementioning
confidence: 99%
“…There are no rulebooks demanding that CEOs should have a degree of post-graduation or that they must have joined college. Nonetheless, not many individuals these days make it to the peak of the business ladder in the absenteeism of formal education (Zandi et al , 2015) (Table III).…”
Section: Related Literaturementioning
confidence: 99%
“…There are no rules demanding that CEOs must have a postgraduate degree or that they should have attended college. Nevertheless, not many people these days make it to the peak of the corporate ladder in the absence of formal education (Zandi, Lok, Aslam, & Singh, 2015). Barker and Mueller (2002) confirmed that there was a significant enhancement in R&D spending linked with a CEO possessing an undergraduate degree, but no significant impact was noticed for advanced levels of educational achievement.…”
Section: Related Literaturementioning
confidence: 99%
“…The Organization and ii) CEO vs. Top Management Teams. In crafting this review paper, we discovered that the literature review on G-CEO and S-CEO has been discussed in majority cases by comparing it with organizational parameters, next in some studies by matching it with characteristics of executives below the level of CEO (including Directors and direct reportees of CEO) (Custódio and Metzger, 2013;Mishra, 2014;Zandi et al, 2015). Hence, it seems reasonable to identify these two as the broad classifications on CEO Generalization/Specialisation.…”
Section: Leadership Perspective On Ceomentioning
confidence: 99%